(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Social Media in Marketing refers to the strategic use of social networking platforms as powerful tools for promoting and enhancing a brand’s visibility, engagement, and overall marketing objectives. This article is about the advantages of utilizing social media in marketing.